Influence of starch pretreatment on yield of cyclodextrins and performance of ultrafiltration membranes - Mimi Sakinah, Abdul Munaim; A.F., Ismail; Osman, Hassan; A.W, Zularisam; Rosli, Md. Illias
The effect of starch pretreatment temperature and exposure time of raw tapioca starch on cyclodextrins (CDs) production and membrane performance using Thermoanaerobacter cyclodextrin glycosyltransferase (CGTase) were investigated in this study. Response surface methodology (RSM) was used to identify the optimum amount of CDs produced. Results indicated that the optimal exposure time and pretreatment temperature for optimum CDs production were 1 h and 70ºC, respectively. Employment of this critical condition (70ºC) as the starch pretreatment temperature, promoted high CDs production and better preservation on the starch granule structure and increased as such as 93% and 94% of swelling power and leached amylose, respectively. In the case of starch pretreatment temperature that is above the critical value (70ºC), such application would apparently increase the solution viscosity and hydraulic resistance that subsequently decrease the membrane flux, despite increasing the CDs yield, suggesting that temperature is a crucial factor in determining the efficiency of CDs production, in particularly in the continuous system.